2021
DOI: 10.48036/apims.v17i2.494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Probiotics to Standard Treatment on Neonatal Jaundice

Abstract: Objective: To compare the mean change in the bilirubin levels with addition of probiotics to standard treatment for the management of neonatal jaundice. Methodology: The randomized controlled trial was undertaken at the Neonatal Intensive Care Unit of the Paediatrics Department, Federal Government Polyclinic (Post Graduate Medical Institute), Islamabad from 1st April to 30th September 2019.  Neonates with hyperbilirubinemia requiring phototherapy were randomly divided into two groups, each having 30 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Several trials have evaluated the effects of probiotics, prebiotics, and synbiotics in neonatal IHB adjunct to phototherapy. Walker-Pizarro et al, in an RCT on the efficacy of Lactobacillus reuteri and Saccharomyces boulardii in neonatal IHB, observed no statistical difference in bilirubin reduction rate consistent with the results of Afzal et al's study (25,26). In this regard, Santosa et al demonstrated no significant effects of probiotics on decreasing serum bilirubin levels (27).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 60%
“…Several trials have evaluated the effects of probiotics, prebiotics, and synbiotics in neonatal IHB adjunct to phototherapy. Walker-Pizarro et al, in an RCT on the efficacy of Lactobacillus reuteri and Saccharomyces boulardii in neonatal IHB, observed no statistical difference in bilirubin reduction rate consistent with the results of Afzal et al's study (25,26). In this regard, Santosa et al demonstrated no significant effects of probiotics on decreasing serum bilirubin levels (27).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 60%
“…Pada penelitian RCT yang dilakukan oleh Afzal et al 19 pada 60 neonatus hiperbilirubinemia dengan berat lebih dari 1,5 kg yang membutuhkan tatalaksana fototerapi pada 7 hari pertama kehidupan. Bayi-bayi tersebut dibagi dua menjadi kelompok intervensi yang menerima 2,5 ml Enterogermina ampule yang mengandung Bacillus clausii secara oral dan kelompok kontrol; kedua kelompok menerima tatalaksana fototerapi.…”
Section: Bahasanunclassified